The relationships between contingent factors and management accounting practices on the use of performance measures among selected exporting small and medium sized manufacturing firms in Malaysia / Ibrahim Morshidi - Morshidi, Ibrahim (2021)
Malaysian’s exporting small and medium sized manufacturing firms are operating under highly competitive and challenging business environment due to the effects of globalization, widespread application of computer-based control in production, as well as the opening up of regional markets. In order to understand the competitive composure of Malaysian exporting SMEs in the global markets, this study investigates the relationships between the contingent factors, the use of management accounting practices and the firms’ usage of performance measures. This study adopts the contingency theory framework to explain the variations found in the firms’ usage of performance measures due to the alignments of these contingent factors and management accounting practices. Data was collected via mailed questionnaires from 78 exporting small and medium sized manufacturing firms in selected industrial hubs of Klang Valley and the states of Perak, Johor, Penang, Negeri Sembilan and Sarawak. The firms were identified from the Federation of Malaysian Manufacturers (FMM) 2009 Directory, MATRADE Malaysian Export Directory of Malaysian Products and Services, 2007 and List of Association Members, Sarawak Manufacturers’ Association (SMA), 2009. The sampling frame comprised of 410 firms in the food and beverages industry, plastic products and resins, furniture and wood related product, chemical and adhesive, iron and steel products electric and electronic and other consumer goods. Seventy-eight (78) questionnaires were returned and useable for further analysis resulting in the response rate of 19.02 per cent. Preliminary analyses were performed using the SPSS statistical method and the subsequent inferential analyses were conducted using the non-parametric variance based Partial Least Squared Structural Equation Modeling (PLS-SEM) statistical method. The study found some significant direct relationships between certain contingent factors and the use of management accounting practices by the firms but the hypothesized alignment between the contingent factors, the use of management accounting practices and the use of performance measures was not fully supported. Although the expected relationships between the contingent variables and the use of management accounting practices and the use of performance measures are not consistent with findings of other studies, the results indicate that the strategic alignments of business strategies, manufacturing technology, management accounting practices, environmental uncertainty, leadership styles and the use of performance measures among the firms are only partially observed in the Malaysian’s context. Therefore, it is concluded that the alignment pattern of contingent factors with management accounting practices and the use of performance measures is not fully observed in the context of exporting small and medium sized manufacturing firms in selected industrial hubs in Malaysia. Hence, the competitive posture of these exporting small and medium sized manufacturing firms is not at par with other SMEs in developing and developed countries